All God's critters - Staines, Bill; Nelson, Kadir (New York Simon & Schuster Books for Young Readers, 2009)
Celebrates how all the animals in the world make their own music in their own way, some singing low, some singing higher.
93102
Keywords: Children's songs, English -- United States; Animal sounds -- Songs and music; Songs